Genotype-phenotype correlations in NTHL1-associated tumour syndrome: case report and literature review (Swiss Medical Weekly, 2025)
NTHL1-associated tumour syndrome, formerly known as NTHL1-associated polyposis, is a rare autosomal recessive tumour predisposition in which biallelic carriers of pathogenic NTHL1 variants develop multiple, predominantly adenomatous, polyps and have an increased risk of colorectal cancer and extracolonic tumour manifestations. The Nth like DNA glycosylase 1 (NTHL1) gene encodes for an enzyme involved in the base excision repair pathway which plays an important role in the maintenance of genomic integrity in the cell.Upon identification of our first Swiss biallelic NTHL1 carrier, we performed a literature survey on mono- and biallelic NTHL1 carriers, followed by genotype-phenotype correlations in order to delineate the clinical manifestations and review current screening recommendations. A comprehensive literature search was conducted to identify all individuals with NTHL1 variants reported since the initial discovery in 2015 to 2022, followed by a genotype-phenotype analysis on a total of 216 individuals, 59 being biallelic and 157 monoallelic NTHL1 carriers. 81.4% of biallelic NTHL1 carriers presented with colon polyps, the majority (69%) exhibiting between 5 and 99 polyps. Interestingly, though not statistically significant, 19% (6/31; p = 0.0766) of carriers homozygous for the recurrent p.Gln90Ter variant displayed a classical (>100 polyps) polyposis phenotype compared to none of the compound heterozygous patients (n = 20); additionally, compound heterozygotes were diagnosed with breast cancer twice as often as homozygous women (75% vs 38.9%, p = 0.0717). Among biallelic carriers, colorectal carcinomas were reported in 50.8% (n = 30; median age at diagnosis: 49 years) and extracolonic malignancies in 55.9% (n = 33), with breast (53.3%), skin (27.1%), endometrial (16.7%) and bladder cancer (8.5%) being the most frequent. Among monoallelic NTHL1 carriers, 15.3% (n = 24) presented with colon polyps and 17.8% (n = 28; median age at diagnosis: 55 years) with colon carcinomas.Timely surveillance measures are essential for early colorectal and breast cancer detection, treatment and prognosis. Prospectively gathered data are needed to further establish and refine clinical guidelines for individuals with NTHL1-associated tumour syndrome.